Environmental Health Risks to Children in Sub-Saharan Africa: A Scoping Review of Evidence and Gaps in Global Interventions - Chitambwe, Tadius C; Susanna, Dewi (UI Scholars Hub, 2025)
Sub-Saharan Africa’s (SSA) children experience a disproportionate burden of environmental health risks, contributing to over half of global under-five deaths despite representing only 27% of live births 1. This scoping review synthesised evidence from sixty-seven (67) eligible studies (2010–2025) to map out environmental exposures affecting children (0–18 years) in Sub-Saharan Africa, and to identify gaps in global interventions. Included studies focused on children (0-18 years) in SSA, addressed one or more of the four predefined environmental exposure domains (air pollution, WASH, toxic chemicals, climate-related risks), and reported on child health outcomes or interventions. Guided by the PRISMA and Arksey and O’Malley frameworks, peer-reviewed articles and organisational reports were identified from WHO, UNICEF, PubMed, and Google Scholar, and scrutinised for exposure-outcome links, study design, and intervention coverage. Evidence was synthesised across four major domains: air pollution, WASH, toxic chemical exposures, and climate-related risks. The results show that household air pollution, unsafe water and sanitation, lead and e-waste contamination, and climate variability consistently contribute to elevated morbidity and mortality among children, particularly those under five years, where most primary data were reported. Despite progress in WASH and emergency response, major gaps persist in air quality monitoring, toxin surveillance, and climate-health integration. Protecting child health in SSA necessitates strengthened multisectoral action across health, environment, WASH, energy, and social protection sectors to enhance monitoring, mitigation, and adaptive responses, ensuring every child’s right to a safe and clean environment. Keywords: Sub-Saharan African children, environmental health risks, pollution, WASH, and climate change